Diseño del proceso contable del comercial peña de ruth peña aguachela, cantón puebloviejo, periodo 2023 - Peña Mendoza, Elena Raquel (2023)
The purpose of the Curricular Integration Work entitled "Design of the accounting process of Ruth Peña Aguachela's Comercial Peña, canton Puebloviejo, period 2023" is to structure an accounting process that meets the needs of the commercial, where it allows the business to record the economic and financial activities, whose purpose is the generation of transparent and reliable information to the agency responsible for tax collection such as the SRI. The methodology used was based on a qualitative approach and by means of a correlational analysis with an Ishikawa model, the direct relationship between the variables was corroborated in order to accept the hypothesis put forward; likewise, techniques such as direct observation and interview were implemented, where the absence of an accounting process in the entity was determined. The discussion frames five phases for the customization of the accounting design: the systematization of the policies, norms and laws, the valuation of the main accounts, the processing of the purchase and sale processes, the evaluation of the daily transactions and the information presented through the structure of the balance sheets. It is concluded that the company presents a deficit in accounting, product of the empirical part in the accounting area; so it is recommended to the owner to analyze the proposed topic, where it is evident that for types of commercial companies it is advisable to opt for a perpetual inventory that facilitates the automatic update of the products with greater demand; through a specialist in accounting and financial matters.